Building the Shape in Sharif Mohieddin Haider Musical Compositions (Al-Academy, 2018)
Sharif Mohieddin Haider worked on composing of musical compositions for the Oud different from the traditional forms known as (Peşrev, Sama'i, Longa… etc.), but they are not clear in building their musical form. This study tackles this issue by revealing the structure of the building of the musical form of these Musical compositions. The importance of this research lies in that it provides an academic scientific study on the important subject of Musical composition forms and the way of constructing them. It helps players and students in the study of Arab music, if they want to write according to their musical form.This research dealt with two topics in its theoretical framework: (The oud instrument in Iraq and the role of Sharif Mohieddin Haider in its musical renaissance), and (the form in music). The research also studied randomly selected samples which represented some of the Sharif Mohieddin Haider’s musical compositions through analyzing them according to a standard designed to achieve this objective, and to arrive a set of results and conclusions, the most significant of which is that most of Mohieddin Haider’s musical compositions for Oud do not go beyond the simple Western forms known as Ternary Form. The results also showed the departure of Sharif Mohieddin Haider from the eastern Maqam that contains a quarter of the musical score in composing these compositions, where he focused on maqams like Nehund and Ajam